Degradation identification and prognostics of proton exchange membrane fuel cell under dynamic load. (January 2022) - Yue, Meiling; Li, Zhongliang; Roche, Robin; Jemei, Samir; Zerhouni, Noureddine
Abstract: Proton exchange membrane (PEM) fuel cell has seen its recent increasing deployment in both automotive and stationary applications. However, the unsatisfied durability of the fuel cell has barriered in the way of its successful commercialization. Recent research on prognostics and predictive maintenance has demonstrated its effectiveness in predicting the system failure and improving the durability of the PEM fuel cell. This paper contributes to developing a degradation identification method for the PEM fuel cell operating under dynamic load. A degradation indicator is proposed based on the polarization model and the nonlinear regression method is applied to extract the degradation feature by segmenting the voltage measurement. To perform prognostics, a machine learning method based on a multi-step echo state network is developed, in which a sliding window is used to recursively reformulate the input sequence with predicted values in the prediction phase. The length of the sliding window is optimized by a genetic algorithm. The proposed method is verified on the experimental PEM fuel cell degradation data and improves the prediction performance on both accuracy and computation speed when comparing with other prognostics methods. Highlights: A degradation indicator of PEM fuel cells is proposed for real-time operation. An enhanced multi-step ESN-based prognostics strategy is adapted for prognostics. The configuration of the proposed algorithm is optimized via a genetic algorithm. The proposed prognostics strategy is validated by the long-term experimental data.